1995
DOI: 10.1016/0167-4889(95)00019-o
|View full text |Cite
|
Sign up to set email alerts
|

The effects of terbium on the accumulation of cisplatin in human ovarian cancer cells

Abstract: In this investigation, we report a relationship between the terbium (Tb3+) binding protein and the accumulation of cisplatin in human ovarian cancer cells. The number of Tb3+ binding sites in cisplatin-resistant C13+ cells is significantly greater by 79% than those in cisplatin-sensitive 2008 cells. Exposure to Tb3+ also increased the cellular accumulation of cisplatin. The accumulation of cisplatin as a function of the Tb3+ concentration in the C13+ cells (0.85%/microM Tb3+) was significantly greater than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the binding of lanthanum ions to the membrane increases membrane permeability hence facilitating the passage of other lanthanum ions [61]. It was further reported that other lanthanides such as gadolinium ion could form pores in erythrocyte membranes [62] while terbium is able to bind to membranes of ovarian cancer cells increasing the accumulation of cisplatin in cisplatinresistant cancer cells [63]. Transport of lanthanum is enhanced by complexation with various ligands, forming species able to diffuse through the plasma membrane and to enter the cell more easily than lanthanum ion.…”
Section: Discussionmentioning
confidence: 98%
“…However, the binding of lanthanum ions to the membrane increases membrane permeability hence facilitating the passage of other lanthanum ions [61]. It was further reported that other lanthanides such as gadolinium ion could form pores in erythrocyte membranes [62] while terbium is able to bind to membranes of ovarian cancer cells increasing the accumulation of cisplatin in cisplatinresistant cancer cells [63]. Transport of lanthanum is enhanced by complexation with various ligands, forming species able to diffuse through the plasma membrane and to enter the cell more easily than lanthanum ion.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, fifteen newly synthesized cerium(III), lanthanum(III) and neodymium(III) complexes with bis-coumarins (13)(14)(15)(16)(17) were characterized, and their cytotoxic activities were tested on a variety of cancer cell lines [46,[49][50]. Significant difference in activity was found.…”
Section: Anticancer Agentsmentioning
confidence: 98%
“…However, the clinical success will depend on whether the opposing effects can be modulated. To this end, it is essential to understand the nature of the duality [14].…”
Section: Biological Effects Of Lanthanidesmentioning
confidence: 99%
See 1 more Smart Citation